Outcomes of Live Kidney Donors Who Develop End-Stage Renal Disease. Issue 6 (June 2016) - Muzaale, Abimereki D.; Massie, Allan B.; Kucirka, Lauren M.; Luo, Xun; Kumar, Komal; Brown, Ryan S.; Anjum, Saad; Montgomery, Robert A.; Lentine, Krista L.; Segev, Dorry L.
Abstract : Background: Kidney donors can develop end-stage renal disease (ESRD) after donation, but the outcomes of those who do remain poorly characterized. Methods: Using United States Renal Data System and Scientific Registry for Transplant Research data, we compared access to kidney transplantation (KT), time from ESRD to listing, time from listing to KT, and post-KT graft failure and death between donors and matched nondonors with ESRD. Results: Among 99 donors between April 1994 and November 2011 who developed ESRD, 78 initially received dialysis (of whom 37 listed for KT, 2 received live donor KT without listing, and 39 never listed for or received a KT), 20 listed preemptively (of whom 19 were subsequently transplanted), and 1 received a preemptive live donor KT without listing or ever receiving dialysis. Donors were listed earlier (median time to listing, 17 months vs 120 for nondonors; P < 0.001), received KT earlier (median waiting time, 2.8 months vs 21.5 for nondonors; P < 0.001), and received 13% live donor, 87% standard criteria, and 0% expanded criteria deceased donor KT (39%, 50%, and 11% in nondonors). Post-KT graft (adjusted hazard ratio, 1.9; 95% confidence interval, 0.9 to 4.1; P = 0.1) and patient (adjusted hazard ratio, 0.7; 95% confidence interval, 0.2 to 2.4; P = 0.5) survival were comparable in donors and nondonors. Conclusions: Our finding that 39 of 99 donors who developed ESRD never listed for a transplant warrants further study to ascertain why these donors with ESRD never gained access to the waiting list. Abstract : The authors compare access to kidney transplantation, and transplant outcome between donors and matched nondonors with ESRD. Thirty-nine of 99 donors who developed ESRD never listed for a transplant warrants further study to ascertain why these donors with ESRD never gained access to the waitlist.